Modelling and Simulation of Multistep Constant Current Fast Charging for Lithium-Ion Batteries Using a PID Controlled Synchronous Buck Converter - Fahmi, Monika; Deni Tri Laksono; Dedi Tri Laksono (PT. Global Research Collaboration, 2026)
High-current fast charging of lithium-ion batteries in electric motorcycles is challenged by current instability, voltage overshoot, and accelerated degradation caused by nonlinear electrochemical and thermal dynamics. Conventional single-stage buck converters exhibit limited capability in maintaining precise current regulation across wide state-of-charge (SoC) variations, thereby constraining both efficiency and operational safety. This study proposes a novel adaptive multistep constant-current (MS-CC) fast charging framework specifically tailored for electric motorcycle applications, implemented using a PID-controlled synchronous buck converter. Unlike existing MS-CC approaches, the proposed method introduces a unified control architecture that dynamically schedules five discrete current levels based on real-time voltage thresholds, enabling seamless transition between charging stages without inducing transient spikes. The system is modeled and validated in MATLAB/Simulink, with PID parameters tuned via the Ziegler–Nichols closed-loop method. Simulation results show that the charging current accurately tracks its reference within 0.25% across all stages, with negligible overshoot and stable transient performance. From a practical standpoint, the proposed strategy aligns with the operational constraints of electric motorcycles, such as compact onboard chargers, limited thermal management capacity, and frequent fast-charging cycles. Furthermore, the method reduces switching and conduction losses, mitigates thermal stress, and enhances overall charging efficiency while preserving electrochemical stability. These findings demonstrate that the proposed MS-CC control scheme not only advances the state-of-the-art in charging control strategies but also provides a viable, implementation-ready solution for next-generation electric motorcycle charging systems.